NUTRITIONAL AND MEDICINAL PROPERTIES OF SEA BUCKTHORN AND COMPREHENSIVE REVIEW OF ITS PHYTOCHEMICAL CONSTITUENTS AND HEALTH BENEFITS - Adil Iqbal; Abdul Jabbar; Hina Mumtaz; Faiza Rafique; Ayesha Shakir; Esha Arshad; Qurban Ali; Maaz Bin Nasim; Muhammad Naveed Mushtaq (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
This review evaluates the medicinal and therapeutic potential of sea buckthorn, a thorny shrub, belongs to a family Elaeagnaceae in the prevention and management of multiple maladies, both acute and chronic. Owing to its nutritional and therapeutic qualities, the plant is utilized throughout the world, but most frequently in Europe and Asia. Preparations derived from sea buckthorn have been widely used in ancient cultures to treat ailments as ulcers, lagging digestion, gastroenteritis, cardiovascular issues, liver disease, tendon and ligament injuries, and skin disorders. Pharmacological and therapeutic properties of Sea buckthorn have been thoroughly studied in recent years utilizing several kinds of in vitro and in vivo models in addition to a small number of clinical trials. Numerous traditional uses of sea buckthorns have been validated by scientific analysis, pharmacological and phytochemical content investigation. It is well known that sea buckthorn exhibits immunomodulatory, anti- inflammatory, and antioxidant properties. Particularly, berries include vitamin C, which supports the immune system, both the seeds and pulp oil provide omegas 3, 6, 7 and 9 are beneficial to the skin, the cardiovascular system, and the metabolism. Given its vast therapeutic and pharmacological potential, sea buckthorn is undoubtedly an essential plant. However, this study’s identification of a number of information gaps will spur further research and development, particularly in the area of sea buckthorn-based nutraceuticals and herbal medicine.